Something blue - Giffin, Emily (New York : St. Martin's Paperbacks, 2011)
Her belief in the power of beauty shattered when her fianc ďumps her for a plain woman, a pregnant Darcy flees to London and struggles to rebuild her glamorous life before realizing that her past methods no longer work.
Keywords: Pregnant women -- Fiction; Americans -- England -- Fiction; Rejection (Psychology) -- Fiction; London (England) -- Fiction; Psychological fiction; Love stories